THE ROLE OF FDG PET/CT BASED HOPKINS CRITERIA FOR THERAPY RESPONSE IN NON-SMALL CELL LUNG CANCER - Lê Nho , Quốc; Lê Phạm Mỹ, Hạnh; Nguyễn Xuân , Cảnh (Journal of 175 Practical Medicine and Pharmacy, 2023)
Objective: Many imaging modalities are extensively applied for diagnosis and follow-up in non-small cell lung cancer (NSCLC). The aim of this study was to evaluate the role of PET/CT (Positron Emission Computed Tomography) with F-18 Fluorodeoxyglucose (FDG) based Hopkins criteria for therapy response in NSCLC. Patients and methods: Retrospective study of NSCLC patients who underwent FDG PET/CT before and after chemotherapy and/or radiation therapy to analyzed the efficacy of FDG PET/CT using the 5 points scale of Hopkins criteria. Results: The study included 23 patients with NSCLC (18 male and 5 female). Before specific treatment, 22 patients with primary lung lesion uptaked FDG at 5 points and 1 patient with 4 points according to Hopkins criteria. After treatment, 5 patients demonstrated primary lung lesion with FDG uptake at 5 points, 2 at 4 points, 2 at 3 points and 14 without primary lung lesions. Six patients (26.1%) showed complete response, 5 (21.7%) partial response, 4 (17.4%) stable disease and 8 (34.8%) progression disease. Conclusions: The pilot study suggested FDG PET/CT based on Hopkins criteria appropriate for assessment of NSCLC treated with chemotherapy and/or radiotherapy.